MODEL PEMBELAJARAN LANGSUNG TERHADAP KETERAMPILAN MENGENAL WARNA DASAR SISWA AUTIS - FAIZAH, NUR (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   The introduction of color in children has several benefits namely, develop intelligence, hone the ability to remember, imagination, artistic, understanding space, cognitive skills, and creative thinking pattern is simple. While autistic children experiencing developmental delays that affect several aspects of children in a familiar environment and learning experiences, which lead to children experiencing barriers to recognize colors as happened in students with autism in SLB AL FALAH Sembayat Gresik. The purpose of this research is to study about the basic skills of autistic children recognize colors before and after intervention using direct learning model. This study uses a pre-experimental type of research. The time used is 10 times with 1 times pretest, posttest 1 times and 8 times of intervention. In the implementation of pretest and posttest child is given a test sheet in the form of children's ability to recognize colors before and after the intervention, in the form match the image, count the number of images with the same basic color, and color the picture as instructed are written. And on the implementation of the intervention recognize the child is given treatment in the form of basic colors, simple flat wake, and the numbers 6 through 9. The design study is one group pretest posttest design with a sample of 7 children. Methods of data collection is done by testing and observation. Analysis of the data is non-parametric statistical analysis using unmarked rank test (Wilcoxon). From the analysis of data acquired Z count 2,368 results with a significant proportion of testing the value of one side (critical value = 5% Z table = 1.64) and test 2 sides (critical value = 5% Ztabel = 1.96) and of hypothesis testing above, it can be concluded that the learning model directly affect the ability to recognize colors basic skills of autistic students in class II SLB AL FALAH Sembayat Gresik.   Keywords: Direct Learning Model, Primary Color